m^2+4m-5
m^2+7m+10

(7(m-2) _ m+2 ) . 2m^2+4m+8
(m^3-8 m^2+2m=4) m-3

2a+3 . (2a^2+3a _ 3a+2) + 4a-1 _ a-1
2a-3 (4a^2+12a+9 2a+3) 2a-3 a

(9x^2+8 _ 1 + 4 ) . 3x-1
(27x^3-1 3x-1 9x^2+3x+1) 3x+1

1

Ответы и объяснения

2013-08-10T01:45:25+04:00
1. m^2+4m-5
D=4^2+4*5=36
m1=(-4+6)/2= 1 
m2= -5
(x-1)(x+5)
m^2+7m+10
D=7^2-4*10= 9
m1= (-7-3)/2 = -5
m2= -4/2=-2
(x+2)(x+5)
((x+5)(x-1))/(x+2)(x+5)=(x-1)/(x+2)
2. 
1)
( (7(m-2))/(m-2)(m^2+2m+4) )  - ( (m+2)/(m+2) ^ 2 ) =
( 7/((m+2)^2)- ( ( m+2)/(m+2)^2 ) = (7-m+2)/(m+2)^2= ( (9-m)/(m+2)^2 ) 
2) ( (9+m)/(m+2)^2 * ( 2 ( m^2+2m+4)/(m-3) ) = (9-m)*2/(m-3) =  (18-2m)/(m-3)
http://cs316727.vk.me/v316727766/d6a2/W8PhtQmEBQo.jpg
http://cs316727.vk.me/v316727766/d698/UwKK0-BP820.jpg